Features and outcome of fetal cardiac aneurysms and diverticula: a single center experience in China. (22nd November 2015) - Zeng, Shi; Zhou, Qichang; Zhang, Ming; Zhou, Jiawei; Peng, Qianghai
Abstract: Objectives: We aimed to describe the prenatal features and clinical outcome of fetal cardiac aneurysms (CA) and cardiac diverticula (CD). Methods: Retrospective single center study reporting on antenatal findings and interventions and clinical outcome of fetuses with CA or CD are assessed in a ten year's period. Results: Thirteen CA and 16 CD identified, mostly located at the cardiac apex. The average size of the CA was significantly larger than that of the CD (223.2 ± 84.4 vs 80.6 ± 57.9 mm 2, respectively; p  < 0.05). The bulge longitudinal strain, systolic strain rate, and diastolic strain rate in CA were significantly lower compared with CD (respectively, −12.9 ± 3.7 vs −20.0 ± 5.4% for strain and −1.3 ± 0.4 vs −2.0 ± 0.5 s −1 for the systolic strain rate, 1.2 ± 0.4 vs 1.9 ± 0.4 s −1 for the diastolic strain rate; all p  < 0.05). CA coincided more frequently with arrhythmia and CD more frequently with pericardial effusion ( p  < 0.05). Adverse outcomes were more likely in children with CA [83.3% (5/6) vs 8.3% (1/12), respectively, p  < 0.01]. Conclusion: Fetal cardiac aneurysms and diverticula are two distinct entities with different morphology and outcome. An isolated fetal CA has a less favourable outcome than fetal CD. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Cardiac aneurysms and diverticula can be detected prenatally by echocardiography. The current literature consists of small series or case reports. What does this study adds? The spectrum and perinatal outcome of fetal cardiac aneurysms and diverticula in a larger series are reported in our center.